SOSIALISASI POLA HIDUP SEHAT DENGAN PROTOKOL KESEHATAN TERHADAP PENCEGAHAN PENULARAN COVID-19 - Dian Puspita; Leni Anggraeni; Rina Wati; Widi Andewi (COVIT (Community Service of Health), 2022)
Until now, Indonesia is still struggling to fight the Covid-19 virus pandemic. The number of positive cases of Covid-19 continues to increase every day. The government always urges the public to follow health protocols because that's what we all need during a pandemic. Of course stopping the spread of the Covid-19 virus will not be easy. For this reason, we are encouraged to increase body immunity so that we can fight the Covid-19 virus. One way to increase body immunity is to adopt a healthy lifestyle. To have a good body condition, a person must have a clean and healthy lifestyle. In this community service activity, the PkM IBN Pringsewu team held socialization activities for clean and healthy living behaviors and maintaining health protocols which aim to provide an understanding of the prevention of Covid-19 as well as clean and healthy living behaviors. The method used in carrying out this socialization activity is using the lecture method by going around to the residents' environment. This activity has the benefit of increasing understanding among residents about the importance of maintaining health, cleanliness, and implementing health protocols in preventing Covid-19. Keywords: Socialization, PHBS, Health Protocol, Covid-19 Prevention.